Penelitian dengan judul Nilai- Nilai Budaya dalam Novel Karena Aku Tak Buta Karya Redy Kuswanto: Kajian Struktural Genetik - Indri Anatya Permatasari (UHAMKA Graduate School Thesis Abstract Collection, 2016)
Research under the title "cultural values in Novel Because I'm Not Blind Work Redy Kuswanto (Structural Genetic Studies)" is a qualitative descriptive peneliyian genetic structural approach. Issues addressed in this study are: (1) How do cultural values based culture form the novel Because I'm Not Blind Kuswanto Redy Work? (2) How does the cultural values of tangible ideas, ideas, or view in the novel Because I'm Not Blind? (3) How do cultural values that tangible behaviors, activities or acts in a novel Because I'm Not Blind? (4) How do cultural values of tangible objects, artifacts or works in a novel Because I'm Not Blind? (5) What cultural values contained in the novel Because I'm Not Blind Redy Kuswanto work in terms of worldview author? The purpose of this study was to decrypt the cultural values portrayed on all the intrinsic elements in the novel Because I'm Not Blind Kuswanto Redy work associated with the background of the author. The results of this study are expected to be useful for Indonesian teachers, students, researchers themselves, and society. This research method is qualitative description, whereas the research approach is genetic structural approach that emphasizes the text as an object of study. The data in this study is a sentence, a collection of sentences, a paragraph or a few paragraphs that make up the piece of the story and not a number. The data source of this research is the novel Because I'm Not Blind Kuswanto Redy works that are published by Pustaka Mandiri PT Triad in January 2015. The data collection method used is literature. The instrument of this study is the researchers themselves to use qualitative data analysis tables refer to qualitative data analysis Philip Mayring. The results of this study are intrinsic elements there are three that are the focus, the characters, plot, and setting. These three elements are mutually reinforcing and together to build a unity of narrative novel Because I'm Not Blind, the author describes the cultural values through the events that build the storyline, the character's mind Zad as the main character, dialogue antartokoh, and foreground-background events, both physical setting and background ambience.